Surat-surat Ternate: Analisis Struktur dan Isi - Syadiidah Syadiidah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
This article discusses the Malay manuscript of Surat Keputusan Ternate as a formal letter that was used in the past. This manuscript tells us a decree handed down by the royal permission Sultan Taajul Malik Amiruddin Iskandar Kaulain Syah to give punishment to Tambuku’s Kingdom because of rebellion against to Ternate. This manuscript contains the inspection violation process, the articles, and punishments for the perpetrators of the rebellion. The King of Tambuku and his commanders get a penalty in the form of exile. To understand this text, philological studies were conducted to produce text editing. The manuscript was transliterated from Jawi’s script to Latin’s script and was edited using the critical method to be easily read and understood. Moreover, the letter would be classified and the form and the structure would be analyzed to know how the previous letter is different from the ancient letter. Furthermore, this journal also described the incident that caused the writing of Surat Keputusan Ternate.Keywords: Malay Manuscript; letter structure; Tambuku; Ternate